Some new species of Mycovellosiella - and PADMANABH MISHRA, SANJAY K. SINGH*, PARAS NATH SINGH (Indian Phytopathology, 2004)
Present paper deals with three new species of Mycovellosiella Rangel, M. dalbergiae, M. subhyalineae and M. xenogrewiae, collected on Dalbergia sisoo (Caesalpiniaceae), Putranjiva roxburghii (Euphorbiaceae) and Grewia tiliifolia (Tiliaceae), respectively.